Active fault‐tolerant control for near space vehicles based on reference model adaptive sliding mode scheme. (17th April 2014) - Zhao, Jing; Jiang, Bin; Chowdhury, Fahmida N.; Shi, Peng
SUMMARY In this paper, an adaptive sliding mode (ASM) scheme is proposed for fault identification and fault‐tolerant control of near space vehicles (NSVs). First, the attitude dynamic model is introduced, and a baseline controller based on reference sliding mode scheme is designed in the case of no faults. Then fault parameterizations with actuator dynamics is presented for several classes of faults: lock‐in‐place, float, hard‐over, and loss of effectiveness. On the basis of adaptive observer design, fault parameters can be accurately estimated on‐line. Furthermore, an ASM fault‐tolerant controller is designed for both cases of actuator dynamic faults and control effector damage. Finally, simulation experiments show that the proposed ASM scheme is able to quickly and accurately identify faults and reconfigure the controller, resulting in excellent overall system performance. Copyright © 2012 John Wiley & Sons, Ltd.